Madagascar : Private Enterprise Development - Mohan, P.C. (World Bank, Washington, DC, 2012)
The objectives of the Financial Sector and Private Enterprise Development (APEX) Credit Project (report no. P5076), which was launched in 1990 and lasted for ten years, was as follows: 1) support small and medium enterprises (SME) through technical assistance and support of the government ' s ongoing restructuring efforts of the economy; 2) improve financial sector efficiency through resource mobilization, improved allocation, and interest rate liberalization; 3) strengthen institutions operating in the financial and SME support sector; and 4) generate new employment opportunities. The project comprises three components : 1) financing of projects in productive sectors promoted by private enterprises; 2) technical assistance to support SME development, staff training, strengthening of Central Bank supervision and monetary management capacities; and 3) establishment of policy conditions concerning the financial sector.